Based on polysaccharide nanocarriers: mechanisms of bioactivity potentiation and latest research progress - Du, Juan; Jin, Chuanli; Dang, Ze; Ma, Ruian; Chen, Chen; Bian, Qinglin; Lv, Peng; Ji, Yanhu; Gao, Weicheng; Liu, Shunhui (Frontiers in Biomaterials Science, 2026)
As nanoscale drug-delivery systems constructed from natural polysaccharides, polysaccharide nanocarriers combine the inherent biocompatibility, biodegradability, and diverse bioactivities of polysaccharides with the unique size effects and functional plasticity of nanomaterials. This review systematically outlines the structural characteristics and application advantages of common polysaccharide nanocarriers, including those based on chitosan, hyaluronic acid, dextran, fructan, starch, and traditional Chinese medicine. Specifically, the review highlights the mechanisms of bioactivity of these nanocarriers in terms of their antitumor effects, immunomodulatory, anti-inflammatory, and antioxidant activities, as well as neuroprotective effects. Polysaccharide nanocarriers can not only improve the therapeutic index of drugs through targeted delivery and stimuli-responsive release but also exhibit intrinsic bioactivities that synergize with the loaded drugs, enabling integrated diagnostic and therapeutic functions. Although the existing research has demonstrated the considerable potential of polysaccharide nanocarriers in treating complex diseases such as cancer, neurodegenerative disorders, and chronic inflammation, challenges in areas such as structure-activity relationship elucidation, scalable production, long-term safety evolution, and clinical translation remain unresolved. Future research should focus on identifying polysaccharide structure-activity relationships, designing intelligent carriers, and expanding interdisciplinary applications to advance the applications of these nanocarriers in precision medicine and the biomedical field.